USM TO STAGE 'NISYA KHALED' PLAY IN UK, ORGANISE COLLOQUIUM IN UK AND EIRE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 12 May 2016 In his visit to the United Kingdom recently, the Universiti Sains Malaysia (USM) ViceChancellor, Professor Dato' Dr. Omar Osman has met and held discussions with 12 fellowship candidates of the USM Academic Staff Training Scheme (ASTS) who are either completing their studies at the Doctoral (Ph.D) level or being posted at advanced laboratories in London, such as at Oxford University, Cambridge University, University of Reading and Imperial College London.